Assessment of Dengue Fever Severity in Hospitalized Patients - Khalid, Beenish; Khalid, Usman (Biological and Clinical Sciences Research Journal, 2025)
Dengue fever, a mosquito-borne viral infection, is a significant public health problem in tropical regions such as Pakistan. Hepatic dysfunction is a frequent complication of dengue infection and may serve as an early marker of disease severity. Objectives: This study aims to assess the severity of dengue fever in hospitalized patients by evaluating liver enzyme derangement and to assess liver function tests (LFTs) as early indicators of disease severity. Methods: This cross-sectional study was conducted at the Department of General Medicine, Sharif Medical & Dental College, Lahore, from July 2024 to December 2024. A total of 75 patients diagnosed with dengue fever, aged 12 to 60 years, were included using a non-probability consecutive sampling technique. Liver involvement was assessed based on ALT/SGPT levels and classified as mild, moderate, or severe. SPSS 22nd version was utilized for analysis of collected data. Results: Among 75 patients, 65.3% were aged 18–40 years, while 34.7% were aged 41–60 years. The majority (61.3%) were male. Liver enzyme derangement was mild in 18.7% of cases, moderate in 74.7%, and severe in 6.7%. The mortality rate was 18.7%, with a significant association between elevated ALT and AST levels and severe dengue cases (p <0.05). However, some studies suggest that platelet count, hematocrit levels, and systemic inflammatory markers may serve as alternative predictors of dengue severity. Conclusion: Liver function tests, particularly ALT and AST levels, can serve as early indicators of severe dengue. However, conflicting evidence suggests that additional biomarkers should be considered to enhance diagnostic accuracy.